Analytical Solution for the Free Vibration Analysis of Delaminated Timoshenko Beams - Ramazan-Ali Jafari-Talookolaei; Maryam Abedi (The Scientific World Journal)
This work presents a method to find the exact solutions for the free vibration analysis of a delaminated beam based on the Timoshenko type with different boundary conditions. The solutions are obtained by the method of Lagrange multipliers in which the free vibration problem is posed as a constrained variational problem. The Legendre orthogonal polynomials are used as the beam eigenfunctions. Natural frequencies and mode shapes of various Timoshenko beams are presented to demonstrate the efficiency of the methodology.